Accommodating Blind Learners Helps All Learners. (2nd January 2016) - Wojton, Mary Ann; Heimlich, Joe; Shaheen, Natalie
ABSTRACT: Museum educators generally design educational programs that they believe accommodate all visitors; however, the reality is that audiences are diverse and some visitors may prefer to access learning through different means. This article shares the lessons learned by the authors to enhance museum learning for blind visitors and how by using these methods, museum educators can create stronger education programs for everyone.